The Effect of Teaching According to the TASC Model on Chemistry Achievement and Systems Thinking of Students in the Second Intermediate Grade - Jabbar, Dr. Rusul Salam (Journal of Innovation in Education and Social Research, 2024)
The research aims to identify the impact of the TASC, as the research population consists of (2415) female students distributed in (15) middle and high schools for girls. Al-Basma School was selected as a sample for the research, and it includes (4) classes for the second intermediate grade. Two classes were randomly selected, (C) experimental and (B) control, with (35) students per class. The equivalence of the two groups was checked with the following variables: (age, prior knowledge test, intelligence, organizational thinking). The researcher adopted two tools: Chemistry Achievement Test and Organizational Thinking Scale, and their psychometric properties were checked. The researcher reached the results that there is a difference between experimental group students who studied on the TASC model and control group students who studied in a non-modern way in chemistry achievement in favor.